Application Of Laboratory Registration Test - Based IT Professionals In University - Sophian, Sophan; Darwas, Rahmadini (Jurnal Sains dan Informatika, 2016)
One of the activities significant performed on laboratory stmik indonesia the is a test laboratory professional.The test followed by students at least level v aimed at to test the ability good office and programming mahasaiswa to compete in the work and yielding resources quality.In addition the test laboratory professional intended as requirements to do comprehensive test .The registration process test labor at the time is still using microsoft office and consequently got a lot of error, and the requirement register directly to the front office.From the data hence writers draw conclusions to make a system information by using language programming visual studio that is visual basic.net.It is expected that the system proposed so will be easier parties admin to perform the process of data processing registration without require a long time.